(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study investigated the prevalence of trypanosome infection in cattle and Red Sokoto (R.S) goats slaughtered at abattoirs in Asaba, Delta State. 304 animals comprising 265 cattle, 39 R.S goats were examined. Blood was collected from the jugular vein of each animal into EDTA containers, placed in cold boxes and transported to the Nigerian Institute for Trypanosomiasis Research (NITR) laboratory in Asaba where standard trypanosome detection methods (STDM), Haematocrit centrifugation technique (HCT) and Buffy coat methods were used to detect trypanosomes and determine Packed Cell Volume (PCV). The result of the investigation showed that seventeen (17) animals were infected giving an overall prevalence of 5.59%. Fifteen (5.66%) of the cattle and two (5.13%) of the R.S goats were infected. Female cattle had higher prevalence of trypanosomiasis (6.78%) than the male cattle (4.76%). Difference in prevalence in female and male cattle was statistically significant (p<0.05). In R.S goats, 6.45% prevalence was observed in the males while no infection was found in the females. Three species of Trypanosoma namely, Trypansoma vivax, T. congolense and T. brucei brucei were recorded in infected animals. T. vivax, T. congolense and T. brucei brucei were found in the cattle while only T. congolense was found in R.S goats. There was a significant difference between the mean PCV value of infected animals and the non-infected animals (p < 0.05). The result of this study clearly indicates the presence of trypanosome species in the abattoir animals.